Pathomorphology of Myocardial Muscle Fibers in Covid-19 - Bustanov Sh.Y; Salomov Sh. N; Mamataliev A.R; Israilov R (Genius Journals, 2022)
This article covers the morphological features of pathological processes that develop in the myocardium muscle fibers during COVID-19 disease. As a Material, 36 deaths from COVID-19 were examined in autopsy of the cardiac myocardium macro - and microscopic. The results show that it has been confirmed that various pathomorphological deviations may develop as a result of damage to the heart with the virus. As a result of the direct influence of the SARS-CoV-2 virus on the myocardium, the development of all common pathological processes in the heart tissue, the procoaguyant and prothrombogenic effect of inflammation developed under the influence of the virus, myocardial ischemia from insufficient oxygenation caused by microtomyr dysfunction, inflammation of hypersensitivity as a result of an attack. . In the material we studied, vacuolar and fatty dystrophy of cardiomyocytes in myocardial muscle fibers under the influence of the SARS-CoV-2 virus, chaos hypertrophy characteristic of cardiomyopathy of muscle fibers, deformity and contracture of muscle fibers in some cases, fragmentalization, breakdown in other cases, and ultimately necrobiosis and local necrosis of cardiomyocytes were observed
Keywords: COVID - 19; virus-SARS-CoV-2; Heart; myocardium